(3OjhGf GdHGNQRjs - (3GdHGNQRj , Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH, CHh GdMSf,J (B467 (3g` s
(3ChdgG (B:s
(3haQb GdUa eNJGdkG Edjg adG jfSi GdYghO GdJj CcOf ef SHH deG QBfj bQjH GdOGQ eeJMfkG CYGOfj LGfHkG SgdkG hCMSf Hj s
(3BNQgG (B:s
(3YqR YdjfG SQjQ edc oYqQj Yf OSJI haQTg Sbi MjGg MjG eqjJ ojSF oCqOGHg HMaTg s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B35 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B778s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs